Imaginary Intelligence Via Satellites - Huseynov, Mugabil; Hashimov, Elshan (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
This article gives basic information about all types of satellites. The types of satellites reveal the functions, purposes and applications. Information is provided on the sections required to use a satellite. The features of reconnaissance satellites are characterized. Analytical factors of satellite imagery, their pros and cons were compared. The role and functions of satellite imagery in current and probable future wars are declared.